Earth‐Abundant CuWO 4 as a Versatile Platform for Photoelectrochemical Valorization of Soluble Biomass Under Benign Conditions - Chuang, Ping‐Chang; Lin, Chin‐Yuan; Ye, Si‐Ting; Lai, Yi‐Hsuan (Small (Weinheim an der Bergstrasse, Germany), 2024)
Here, a nanosheet‐structured CuWO 4 (nanoCuWO 4 ) is demonstrated as a selective and stable photoanode for biomass valorization in neutral and near‐neutral solutions. nanoCuWO 4 can be readily prepared by a solid phase reaction using nanosheet‐structured WO 3 as the template. Several substrates, including glucose, fructose and glycerol, are investigated to reveal the wide applicability of nanoCuWO 4 . The activity and product distribution trends in biomass valorization are investigated at different pH by taking advantage of the promising stability of nanoCuWO 4 in a wide pH range. Product analyses confirm that formate production with a Faradaic efficiency (FE) of 76 ± 5% and glycolate production with an FE of 61 ± 8% can be achieved by glucose and fructose valorization at pH 10.2, respectively. On the other hand, glyceraldehyde and dihydroxyacetone (DHA) are the main products in the glycerol valorization, accounting for an FE of over 85% at pH 7. Notably, nanoCuWO 4 has the highest FE of DHA in photoelectrochemical (PEC) glycerol valorization compared to WO 3 and BiVO 4 at neutral pH. The oxidation routes and mechanism of glycerol valorization on nanoCuWO 4 are also under investigation. The co‐production of H 2 and value‐added chemicals is finally demonstrated using a photovoltaic cell connected to a nanoCuWO 4 ‐based PEC glycerol valorization system.